Zjištění existence finančních synergických efektů konsolidujících jednotek ve vybraném odvětví - Fridrichová, Michaela (Vysoké učení technické v Brně. Fakulta podnikatelská, 2019)
Diplomová práce je zaměřena na zhodnocení existence finančního synergického efektu u konsolidujících subjektů v odvětví stavebnictví. Za tímto účelem budou navrženy tři vhodné finanční ukazatele, které budou vypočteny zvlášť pro mateřský podnik a koncern. Následná komparace těchto hodnot nám umožním učinit závěr, zda ve zkoumaném odvětví byly dosaženy pozitivní finanční synergické efekty či nikoliv.

The master’s thesis aims to evaluate the existence of the financial synergistic effect concerning consolidating companies in the construction industry area. For this purpose three appropriate financial indicators, which are to be calculated separately for the parent company and the concern, will be proposed. The subsequent comparison of these values will enable us to determine if the positive financial synergistic effects were achieved in the researched area.
Determining The Existence of Financial Synergy Effects of Consolidating Units in The Selected Industry
Keywords: fúze; akvizice; synergie; synergický efekt; koncern; holding; konsolidace; konsolidační pravidla; merger; aquisition; synergy; synergistic effect; concern; holding; consolidation; consolidation rules